Improving Facial Emotion Recognition in Schizophrenia: a Controlled Study Comparing Specific and Attentional Focused Cognitive Remediation - Gaudelus, Baptiste; Virgile, Jefferson; Geliot, Sabrina; , The GAÏA/RECOS Study Team; Franck, Nicolas; Dupuis, M.; Hochard, C.; Josserand, AC.; Koubichkine, A.; Lambert, T.; Perez, M.; Rouyre, B.; et al. (Frontiers in Psychiatry, 2016)
Cognitive impairment associated with schizophrenia are very frequent. Deficits associated with cognitive impairment may impact both neurocognition and social cognition, including facial emotion recognition. These deficits significantly impair functional recovery, and also the social and vocational rehabilitation of people with schizophrenia. Previous studies in this area clearly demonstrated the interest of cognitive remediation to improve neurocognitive and social cognitive functioning in schizophrenia. They also established clear links between facial emotion recognition skills and attentional processes. The present study compares the GAÏA s-face program (GAÏA arm), which focuses on facial emotion recognition processes, with the RECOS program (RECOS arm), a neurocognitive remediation therapy focusing on selective attention. Forty people with schizophrenia were randomly distributed between each study arm and assessed pre- (T1) and post- (T2) therapy. The single blind assessment focused on facial emotion recognition (the main criteria), symptoms, social and subjective functioning, and neurocognitive and social cognitive performance. Both programs were conducted by nurses after a three day training session. The study showed a significant improvement in facial emotion recognition performance in both groups, with a significantly larger effect in the GAÏA arm. Symptoms and social functioning also improved in the GAÏA arm, and certain neurocognitive and social cognitive processes improved in both study arms. Further studies are recommended, with larger population samples and a follow up assessing the long term preservation of these improvements.